(untitled) (Global Journal of Science Frontier Research, 2023)
This study aimed to evaluate the possible histological and ultrastructural changes of liver induced by methomyl pesticide exposure and estimation the possible protective effect of ginger extract for hepatic damage in rats. Ginger is used worldwide primarily as a spicy condiment and of the herbal sources of natural protection from contamination and oxidative stress thus play an important role in chemoprevention of liver diseases. Methomyl is one of the most frequently prescribed pesticides, that are used as a pesticide. It is characterized as a highly toxic compound and has been reported to cause multiple organs damage. Fifteen male albino rats were allocated into 5 main groups. (3 rats in each); one served as control and the four remained groups were for different treatments. GC-MS analysis of ginger extract revealed the content of gingerol, quercetin (3.20%), limonene and zingiberene. Treatment of methomyl treated rats with ginger extract maintained serum ALP, AST& ALT levels and reduced the damage effect with protective efficacy against pesticide induced hepatotoxicity, which appears also more effective than its therapeutic application.